The influence of liquidity, profitability, company size, company growth and company age on company value (Case study on food and beverage companies listed on the Indonesian Stock Exchange period 2018 - 2022) - Enzela, Monika; Simorangkir, Enda Noviyanti; Anastasia, Anastasia; Lumbantoruan, Novitasari; Wahyuni, Putri (Journal of Economics and Business Letters, 2024)
The aim of carrying out this research is to determine the influence of Liquidity, Profitability, Company Size, Company Growth and Company Age on the Value of Companies in the Food and Beverage subsector listed on the Indonesia Stock Exchange for the 2018-2022 period. This research approach is based on a quantitative approach because this research has a clear and orderly flow. This type of research is a type of quantitative descriptive research. The nature of this research is descriptive explanatory. In this research, the population used is all 26 food and beverage companies listed on the Indonesia Stock Exchange from 2018 to 2022. Sampling: Using the purpose sampling method, namely a sampling technique with certain considerations, 85 research samples were obtained. The research results show that there is no partially significant influence between Liquidity and Company Value. There is a partially significant influence between Profitability and Company Value. There is no partially significant influence between Company Size and Company Value. There is a partially significant influence between Company Growth and Company Value. There is no partially significant influence between Company Age and Company Value. Liquidity, Profitability, Company Size, Company Growth and Company Age simultaneously have a significant effect on Company Value.